2018
DOI: 10.1111/ejn.14103
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the effect of cannabinoid type 1 receptor deletion on locus coeruleus‐norepinephrine neurons and corticotropin releasing factor‐mediated responses

Abstract: Cannabinoids are capable of modulating mood, arousal, cognition and behavior, in part via their effects on the noradrenergic nucleus locus coeruleus (LC). Dysregulation of LC signaling and norepinephrine (NE) efflux in the medial prefrontal cortex (mPFC) can lead to the development of psychiatric disorders, and CB1r deletion results in alterations of α2- and β1-adrenoceptors in the mPFC, suggestive of increased LC activity. To determine how CB1r deletion alters LC signaling, whole-cell patch-clamp electrophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 94 publications
1
12
2
Order By: Relevance
“…In a recent whole-cell patch-clamp electrophysiology study conducted on LC brain sections taken from mice lacking the CB1r (CB1r-KO), it was demonstrated that male CB1r-KO mice had heightened LC-NE activity compared to female CB1r-KO mice and to WT mice. This was evident as increased NE cell excitability in male CB1r KOs, whereas there were no significant changes in CB1r-KO females (Wyrofsky et al, 2018). Further support for the sex differences observed in this study were corroborated by NE ELISA, in which there was increased NE in CB1r-KO males compared to CB1r-KO females and WT controls (Wyrofsky et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…In a recent whole-cell patch-clamp electrophysiology study conducted on LC brain sections taken from mice lacking the CB1r (CB1r-KO), it was demonstrated that male CB1r-KO mice had heightened LC-NE activity compared to female CB1r-KO mice and to WT mice. This was evident as increased NE cell excitability in male CB1r KOs, whereas there were no significant changes in CB1r-KO females (Wyrofsky et al, 2018). Further support for the sex differences observed in this study were corroborated by NE ELISA, in which there was increased NE in CB1r-KO males compared to CB1r-KO females and WT controls (Wyrofsky et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…It was reported in this study that cannabinoid receptor type 1 (Cnr1) deletion resulted in increased locus‐coeruleus norepinephrine excitability in male but not female mice. The study also reported increased norepinephrine, tyrosine hydroxylase and corticotrophin hormone levels in male but not female Cnr1 knockout mice (Wyrofsky et al., ). Both of these findings support the hypothesis that the endocannabinoid system is recruited to a greater extent in males than females during acutely stressful experiences, and may therefore provide buffering against short and long‐term negative health effects of traumatic or severe stress for males more so than females (Ney, Matthews, Bruno, & Felmingham, ).…”
mentioning
confidence: 87%
“…The study by Wyrofsky et al. () further suggests that phasic regulation of stress hormones is more strongly influenced by endocannabinoid signalling in males compared to females, and also further suggests that the endocannabinoid “buffer” towards stress may be reduced in females compared to males. This study therefore adds further evidence that differences in endocannabinoid signalling between the sexes may explain the discrepancy observed in clinical prevalence of stress and anxiety disorders following severe stress or trauma.…”
mentioning
confidence: 98%
See 2 more Smart Citations